The Effect of Giving Soy Milk on the Sleep Quality of Premenopause Women in Judiciary Badiklat Environment in 2023 - Claranita Siburian; Rukmaini; Bunga Tiara Carolin (STRADA : Jurnal Ilmiah Kesehatan, 2023)
The premenopausal phase is a phase marked by changes from the fertile period to the absence of conception, which is the phase before women who experience premenopausal syndrome will experience several symptoms, including hot flush, irregular menstruation, heart palpitations, discomfort when urinating, and sleep disturbances. To determine the effect of giving soy milk on the sleep quality of premenopausal women in the Public Prosecutor's Office in 2023. Quasi-experimental research (quasy experimental) with pre-experimental design type one group pretest-posttest. The sampling technique was taken using the method purposive sampling with a total sample of 23 premenopausal women. The data analysis used in this research is univariate and bivariate analysis using the T-test. Based on univariate analysis, it was found that the average sleep quality score of premenopausal women before consuming soy milk was 8.70, while the average sleep quality score of premenopausal women after consuming soy milk was 3.91.